ANALYSIS OF MOTIVATION, CAREER PATH AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE IN THE COMMUNICATIONS AND INFORMATICS SERVICE MEDAN CITY - Siti Normi (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2024)
This study aims to determine and analyze the Effect of Motivation, Career Path and Work Discipline on the Performance of Employees of the Communication and Information Agency (DISKOMINFO) of Medan City. The research sample was 45 respondents. This research was conducted using quantitative research methods. The results showed that motivation, career path and work discipline In this study the data analysis technique used was multiple linear regression analysis which showed that partial motivation did not have a significant effect on employee performance at the Medan City DISKOMINFO Office, the career path partially had a positive and significant effect on employee performance at the Medan City DISKOMINFO Office, Work discipline partially has a positive and significant effect on employee performance at the Medan City DISKOMINFO Office. The hypothesis testing simultaneously shows that motivation, career path and work discipline together have a significant effect on employee performance at the Medan City DISKOMINFO Office with a significant probability of < 0.05 each and has an influence of 0.632 (63.2%).